Facts physics on the Background of philosophy - Janik, Jerzy A. (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2015)
This article is drafted on the basis of three complementary essays by Professor Jerzy Janik. The author takes a look at selected issues in the field of quantum mechanics – especially the problem of quantum superposition and supersymmetry – from perspective of great philosophical systems. The author draws attention to the fact that some of these issues reflect old philosophical problems (e.g., empiricism vs rationalism), and – in some cases – philosophical perspective may save interpretations of quantum mechanics from paradoxes.